2018
DOI: 10.1038/s41598-018-30168-4
|View full text |Cite
|
Sign up to set email alerts
|

Co-expression of Cancer Stem Cell Markers OCT4 and NANOG Predicts Poor Prognosis in Renal Cell Carcinomas

Abstract: Many renal cancer patients experience disease recurrence after combined treatments or immunotherapy due to permanence of cancer stem cells (CSCs). This study was conducted to evaluate the expression patterns and clinical significance of octamer-binding transcription factor 4 (OCT4) and NANOG as the key stem cell factors in renal cell carcinoma (RCC). A total of 186 RCC tissues were immunostained on a tissue microarray (TMA) for the putative CSC markers OCT4 and NANOG. Subsequently, the correlation among the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(57 citation statements)
references
References 44 publications
4
53
0
Order By: Relevance
“…Similarly, Wang et al and Rasti et al reported an association between high Oct4 expression and poor prognosis and metastasis in hepatocellular and renal cell carcinomas, respectively [22,23]. On the other hand, Matsuoka et al suggested that Oct4 might repress the tumorigenic potential of GC cells.…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, Wang et al and Rasti et al reported an association between high Oct4 expression and poor prognosis and metastasis in hepatocellular and renal cell carcinomas, respectively [22,23]. On the other hand, Matsuoka et al suggested that Oct4 might repress the tumorigenic potential of GC cells.…”
Section: Discussionmentioning
confidence: 93%
“…Tumor cell reprogramming experiments exert rather conflicting effects on malignant progression. On the one hand, reprogramming leads to a loss of oncogenicity [ 169 , 170 ] and the suppression of metastasis [ 171 , 172 , 173 ], which is associated with MET, while, on the other hand, the expression of reprogramming factors is associated with a poor disease prognosis [ 172 , 174 , 175 , 176 ]. Thus, induction of EMT using reprogramming factors and the potential of this approach as potential antitumor therapy requires further studies and a deeper understanding of the molecular mechanisms underlying the relationship between pluripotency and cell plasticity.…”
Section: Cell Plasticity and Cancer Progressionmentioning
confidence: 99%
“…As mentioned earlier, CITED2 directly or indirectly regulates expression of key stem cell transcription factors, OCT4, Nanog, Klf4 and Tbx3. These transcription factors are also known to be key players in cancer stem-like cells (112)(113)(114)(115). Therefore, it is possible that CITED2 serves a key role in cancer stem cell function.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%